2022
DOI: 10.1007/s10577-021-09678-x
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of kinetochore proteins measured by FRAP analysis in living cells

Abstract: The kinetochore is essential for faithful chromosome segregation during mitosis and is assembled through dynamic processes involving numerous kinetochore proteins. Various experimental strategies have been used to understand kinetochore assembly processes. Fluorescence recovery after photobleaching (FRAP) analysis is also a useful strategy for revealing the dynamics of kinetochore assembly. In this study, we introduced fluorescence protein-tagged kinetochore protein cDNAs into each endogenous locus and perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(86 reference statements)
1
7
0
Order By: Relevance
“…We found that Mini-CENP-C was sufficient for CENP-C function. This further supports our previous observations that two CENP-C functional domains, the Mis12- and CENP-A-binding domains, are dispensable for CENP-C function in chicken DT40 cells (Hara et al, 2018; Watanabe et al, 2019; Watanabe et al, 2022). Given that the Mis12- and CENP-A-binding domains are related to mitotic kinetochore functions, our results lead to an intriguing idea that CENP-C plays no direct essential roles in kinetochore function during mitosis in tissue culture cells.…”
Section: Discussionsupporting
confidence: 92%
“…We found that Mini-CENP-C was sufficient for CENP-C function. This further supports our previous observations that two CENP-C functional domains, the Mis12- and CENP-A-binding domains, are dispensable for CENP-C function in chicken DT40 cells (Hara et al, 2018; Watanabe et al, 2019; Watanabe et al, 2022). Given that the Mis12- and CENP-A-binding domains are related to mitotic kinetochore functions, our results lead to an intriguing idea that CENP-C plays no direct essential roles in kinetochore function during mitosis in tissue culture cells.…”
Section: Discussionsupporting
confidence: 92%
“…Depletion of CENP-C has been shown to be compatible with short-term retention of very significant levels of CCAN subunits in DT40 cells ( Hori et al., 2008 ). Furthermore, CENP-C displays slow but significant turnover at interphase kinetochores in DT40 chicken cells, contrary to CCAN subunits CENP-H and CENP-T, which are essentially immobile ( Watanabe et al., 2022 ). Thus, CCAN may depend on CENP-A for its localization in addition to CENP-C, and previous work points to CENP-N as a plausible mediator of these additional interactions ( Carroll et al., 2009 , 2010 ).…”
Section: Discussionmentioning
confidence: 97%
“…We have previously demonstrated that CENP-C–CENP-A nucleosome interaction does not occur in interphase chicken DT40 cells, but CENP-C binds to the CENP-A nucleosome upon CDK1-mediated CENP-C phosphorylation during mitosis (Ariyoshi et al ., 2021; Watanabe et al ., 2019; Watanabe et al , 2022). We have also demonstrated that CDK1 mediated CENP-C phosphorylation facilitates the CENP-C–CENP-A interaction in human mitotic cells (Watanabe et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%